Is Democracy Halal or Haram? A Critical Examination of the Democracy Debate in Nigeria - Abdulkadir Salaudeen; Muftau Abidemi Balogun (Penerbit Hellow Pustaka, 2025)
Is democracy halal or haram and can Muslims participate? There are three major perspectives. At one end of the spectrum is a school of thought that argues democracy is disbelief—both in its specific and general sense. At the other extreme end is another jurisprudential school that views democracy to be at par with Islam. This school argues that like other typologies of democracy, there exists Islamic democracy. In the middle of the spectrum is the third perspective. It argues that democracy is a necessity in a multi-religious country with no state religion (like Nigeria) where the Sharia is entirely not applicable or only applicable to personal statues issues like marriage and inheritance. Evidences marshalled by advocates of each of these scholarly perspectives are worthy of discussion. Without questioning the scholarship of advocates of other perspectives, this paper takes the middle course. It argues, focusing on Nigeria, that democracy is a necessity that should not be blindly rejected. Conceptually, it finds that democracy is not intrinsically kufr (disbelief). It concludes with a caveat that democracy does not, in any case, substitute the Sharia. For some overriding public interests, it recommends that Muslims in Nigeria should participate in their country’s politics.